Supercapacitors - Theoretical and Practical Solutions 2018
DOI: 10.5772/intechopen.71003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Aqueous Ion Solution/Tube-Super Dielectric Material-Based Capacitors as a Function of Discharge Time

Abstract: The discharge time dependence of key parameters of electrostatic capacitors employing a dielectric composed of the oxide film formed on titanium via anodization, saturated with various aqueous ion solutions, that is tube-super dielectric materials (T-SDM), was thoroughly documented for the first time. The capacitance, dielectric constant, and energy density of novel paradigm supercapacitors (NPS) based on T-SDM saturated with various concentrations of NaNO 3 , NH 4 Cl, or KOH were all found to roll-off with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…The primary role of the separator in EDLC is to prevent shorting. Notably, there is no separator in any of the previous SDM studies [ 1 , 2 , 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and no shorts were ever detected.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The primary role of the separator in EDLC is to prevent shorting. Notably, there is no separator in any of the previous SDM studies [ 1 , 2 , 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and no shorts were ever detected.…”
Section: Discussionmentioning
confidence: 95%
“…A simple test of the postulate was conducted. A form of super dielectric material (SDM), a recently invented class of materials [ 1 , 2 , 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], was placed on the outside of several parallel plate capacitors. In all cases the core structure, classically considered “the capacitor”, consisted of two titanium metal electrodes with a thin sheet of low dielectric constant (<200) material between.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in Fig. 8 are the results, described in more detail elsewhere [22][23][24][25] for NPSupercapacitors based on aqueous KOH solutions filling vertical tubes in the oxide layer of anodized titania (T-SDM). An extrapolation of the performance of those capacitors appears to surpass that of even lithium ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…This was tested and found accurate in earlier work [3,4]. Other work showed that, as predicted by the model, high dielectric constants would be found for salt water saturated fabric [5], for salt water saturated nano-tubes on the surface of anodized titania [6], for porous solids saturated with various salts [7,8], for fumed silica gels containing salt water [9], for water saturated with salts other than NaCl such as KOH and NH 3 Cl [10]. Other studies show that both metal and carbon can be used as the electrode material [2], and for non-aqueous polar fluids such as DMSO containing dissolved salts, etc.…”
Section: Introductionmentioning
confidence: 99%